AI Fatigue and Mental Health Implications: A Comprehensive Literature Review - Sosiński, Piotr; Piasecka, Natalia (Quality in Sport, 2026)
Introduction. The quick use of artificial intelligence (AI) in healthcare, technology, and businesses brings benefits like faster work and helpful decision support. However, it also creates new problems, causing worse mental health, burnout, and something called "AI fatigue". This means workers feel stressed by the technology, overwhelmed by too much information, anxious about AI capabilities, and tired from constantly having to adapt to new systems. Materials and methods. This review summarizes 22 studies published between March 2025 and March 2026. The researchers used different methods, such as surveys of hundreds of people, interviews, and advanced data models. The studies included many types of workers, such as doctors, technology professionals, factory workers, and office employees. Literature review. The studies show that AI can sometimes help workers, for example, by saving doctors time on paperwork. But often, poorly designed AI makes stress worse. The biggest reason for AI fatigue is that it increases the workload, creating new tasks like monitoring the system instead of removing work. Other major problems include a lack of help from managers, confusing AI systems, and not enough training. Conversely, workers feel much better when their company supports them, when they are trained well, and when the AI is clear and easy to understand. Keeping human control over the AI is also very important for reducing stress and protecting professional independence. Summary and Conclusions. AI fatigue is a serious and measurable problem, but it can be managed with the right approach. The review clearly shows that preventing this fatigue is the responsibility of companies and AI designers, not the individual workers. To successfully use AI, organizations must treat it as a major workplace change. They must protect their employees' well-being and not just focus on making them work faster.